Customer Satisfaction: A New Marketing Variable for Indian Petroleum Companies - Bhattacharya, Sujoy; Goel, Anuj (Journal of Commerce and Trade, 2020)
The research was carried out using a questionnaire which was presented to the respondents, who were customers of the selected companies. Indian petroleum companies in recent years are going through a phase of turmoil as far as product marketing is concern. Since inception, they were operating in an oligopolistic environment with profit margin guaranteed by Government of India. Indian companies started losing their market share to their competitors over the years. Moreover, introduction of world best practices by MNCs and private players in India has also increased the expectation of Indian consumer from the petroleum companies. Thus a new marketing variable for Indian petroleum companies called “Customer Satisfaction” was born. Decontrolling, allowing private participation and availability of cleaner, greener and cheaper alternative fuels in the open market has made Indian petroleum market a very competitive place. Unlike other consumable products, petroleum products marketed in India by any marketer has no distinct attributes to differentiate it from other marketers. In absence of any distinct product features & price differential, this new marketing variable becomes very important for Indian petroleum companies to highlight them out w.r.t. their competitors. Classification-JEL : E51, C58